Adaptation of the compliance and belief scales to Turkish for patients with chronic heart failure [Kronik kalp yetersizliǧi olan hastalar için inanç ve uyum ölçeklerinin Türkçeye uyarlanmasi] - (:unkn) unknown (My University, 2010)
Objectives: We evaluated the validity and reliability of the Turkish versions of the Beliefs about Medication Compliance Scale (BMCS), Beliefs about Dietary Compliance Scale (BDCS), and Beliefs about Self-Monitoring Scale (BSMS) for patients with chronic heart failure (CHF). Study design: After language and content validity studies, the Turkish versions of the three scales were administered to 80 patients (47 men, 33 women; mean age 59.3±12.5 years; range 24 to 79 years) with CHF. Internal consistency of the scales was assessed using the Cronbach's alpha coefficient. Test-retest reliability was assessed using the interclass correlation coefficient measured from two consecutive interviews interspersed by 15 days. Results: There were no significant differences between the two interviews with respect to the total scores of the benefit and barrier subscales of each scale (p>0.05). Cronbach alpha coefficients of the benefit and barrier subscales at the first interview were 0.74 and 0.59 for the BMCS, 0.71 and 0.58 for the BDCS, and 0.77 and 0.68 for the BSMS, respectively. Interclass correlation coefficients for test-re-test reliability for the benefit and barrier subscales were as follows: 0.90 and 0.91 for the BMCS, 0.86 and 0.86 for the BDCS, and 0.90 and 0.93 for the BSMS, respectively. Conclusion: O ur fi ndings s uggest t hat a ll t hree scales have high validity and reliability and can be used as valid and reliable instruments in Turkish patients with CHF.
Keywords: Heart failure/drug therapy/diet therapy/nursing; Patient compliance; Questionnaires; Validation studies